Experiences of Seeking Antenatal Care and Delivery Among Teenagers in Kibuku District, Uganda - Rebecca Namusana; Josephine M. Namyalo; Emmanuel D. Otieno; Robert K. Basaza (Journal of Research & Health, 2022)
Background: Uganda is ranked 14 out of 54 countries in Africa with the highest level of teenage pregnancy. The teenage pregnancy rate in Kibuku District in 2016 was 35.8%, high above the average rate in Uganda (25%) and also above rural areas in Uganda (27%). Unfortunately, there is limited information on the experiences of seeking antenatal care and delivery among teenagers. This paper explored teenagers’ experiences seeking services at health facilities in the Kibuku district, Eastern Uganda. Methods: This study used a phenomenological design. Data were collected using in-depth interviews with 27 teenagers aged 14-19 years seeking antenatal care (ANC) or those who had delivered. The teenagers were purposively selected to participate in the study. Data collected was thematically and inductively analyzed through coding. Results: The study showed that most teenage mothers knew the importance of seeking ANC and delivery from a health facility. Unfortunately, few sought services early due to some experiences, including financial constraints, support from their caregivers (husbands and parents), medication, and health education. The teenagers were motivated to attend ANC and were treated well by health workers. However, most teenagers did not have the decision-making power to seek care. Conclusion: Teenage mothers knew the importance of seeking ANC and delivery at health facilities. Their experiences with the health facilities also contributed to the health-seeking behavior of the teenagers, including the comfort received by the girls at the facility, the medication administered, how they were treated by the health workers and the availability of utilities. Health and social workers could consider sensitizing teenagers and their caregivers about the delicate nature of their health when pregnant to make personal decisions.